(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Short story had been an ancient art form and even today it has an effectiveness of its own stand. Aravind Adiga‟s Between The Assassinationsis a short story collection which is a landmark of Postcolonial formulations along with the inception of Feminism and Marxism. The entire collection is a reflection of the Postcolonial era with the sour consequences of the imperial rule in India. It also exposes the caste-based society and the intercommunal relations of modern India.